Vapor Pressures and Enthalpies of Combustion of the Dihydroxybenzoic Acid Isomers - Manuel J S Monte (2010)
The Knudsen mass-loss effusion technique was used to measure the vapor pressures at different temperatures of the following dihydroxybenzoic acids: 2,3-dihydroxybenzoic acid, between (345.22 and 363.18) K; 2,4-dihydroxybenzoic acid, between (376.22 and 392.11) K; 2,5-dihydroxybenzoic acid, between (372.14 and 388.92) K; 2,6-dihydroxybenzoic acid, between (347.14 and 365.17) K; 3,4-dihydroxybenzoic acid, between (387.12 and 403.26) K; and 3,5-dihydroxybenzoic acid, between (345.22 and 363.18) K. From the temperature dependences of the vapor pressure of the crystalline compounds, the standard (p(0) = 10(5) Pa) molar enthalpies and Gibbs energies of sublimation, at T = 298.15 K, were derived. For each of the six isomers the standard (p(0) = 0.1 MPa) molar enthalpy of formation in the crystalline phase was derived from the experimental standard molar energy of combustion, in oxygen, measured by static-bomb combustion calorimetry at T = 298.15 K. The combination of the standard molar enthalpy of formation in the crystalline phase with the standard enthalpy of sublimation yields the standard molar enthalpy of formation in the gaseous phase of the studied compounds.